Interfacial phenomena and colloid stability. Volume 1 : basic principles - Tadros, Tharwat F., 1937- (Interfacial Phenomena and Colloid Stability, 2015)
Interfacial Phenomena and Colloid Stability deals with the fundamental aspects of interfacial phenomena, which form the basis of applications of interface and colloid science to various disperse systems. These include suspensions, emulsions, nano-dispersions, wetting, spreading, deposition and adhesion of particles to surfaces. This book is valuable for research scientists and PhDs. investigating various aspects of interface and colloid science.